Sikap Wanita Dalam Menghadapai Perubahan Fisik Pada Masa Pre menopause Di Desa Kajarharjo Kalibaru Banyuwangi - Vonny Nurmalya Megawati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2010)
At this time, premenopause is the matter that women are afraid of it. Because some rumours tell us that the women get some problems in this case that they are’nt happy and will be in 40 years old. The aim of this research is to know “the women’s attitude face physic changing in premenopause case”. The research is done by descriptive design with approach quantitative. Spreading questionnarie is given to 96 premenopause women. Subject is drawn from population by simple random sampling. Spreading questionnarie is done to know the deepest knowledge about reasearche and make tabulation on august 24th 2009. The result of research premenopause women shows us 71 responder of positive attitude(73,96%) and 25 respondent of negative attitude (17,99%). The anaylisis has just removed data from questionnarie to the next table and getting presentation is divided between right answers amount and questions amount, the next it is times 100% and the data is intrepreted by attitude criteria. The conlusion is the woman’s attitude takes effects to physic changing and emotional changing in premenopause time. Hopely, the women’s premenopause improve their good knowledge from electronic media and mass media. The next, the health officer has still an important role to keep in giving information.